Efficient Deployment of UWB Anchors for Wide-Area Positioning Coverage using Bipartite Graph - Yang, Tzu-Yi; Yu, Meng-Lin; Wu, Ruey-Beei (IEEE access, 2023)
Indoor mobile robots have been developed rigorously, with more diversified functions and wide applications. The research of indoor robot positioning systems is increasingly critical, and UWB is one of the most accurate methods. However, due to its short reception range, current UWB systems are limited to small activity spaces. Two important questions must be answered to enable UWB systems to be used in a wider area. How many anchors does it need? Where to deploy these anchors? For the first time, this study converts the problem of deploying anchors into finding an ensemble of bipartite graphs. The problem is an np-hard problem, which will be addressed in the study. Nevertheless, the study presents a systematic approach to efficiently solving the number and placement of UWB anchors. The generalized method applies to all places where UWB anchors can be deployed, regardless of spatial shape or size constraints. Moreover, a systematic approach can be used when the total number of UWB anchors is limited; the process can find where to place the anchors so that the robot can be positioned within the maximum range. This method enables the UWB indoor positioning system to be widely and efficiently applied in more fields. Experiments were also conducted to verify the feasibility of this method.